THE IMPLEMENTATION OF SCREENCAST O’MATIC VIDEO IN TEACHING LISTENING SKILL - Kamiliyanto, Dimas; Maulana Yusuf Aditya; Moh. Hafidz (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2021)
This study aims to know the implementation of Screencast O’matic video in teaching learning listening class, the researcher was chosen video screencast O’matic as media to deliver the material to the students. This study was descriptive qualitative research and conducted on Jun 21th – 22th, 2020. The participants of this research were the English teacher and the students of X IPA 1 at SMAS Islam YKHS Sepulu. The data were obtained by observing the students, the teacher, and the implementation of Screencast O’matic video in the listening class by making a transcript and screenshot of the result. The research finding indicates that the students like Screencast O’matic video because help them to know and learned about how to summarize, find the main idea from the video narrative, get a new vocabulary, how to speak like a native speaker and so on. The result of the observation indicates that the implementation of Screencast O’matic video in listening class makes the students more enthusiastic about the material and they can deliver what they have been heard from the video using their own words. Thus, Screencast O’matic video can be used as one of the alternative media for teaching students’ listening skill in a fun way.